IMPACT OF PAKISTAN-MALAYSIA FTA ON INDONESIAN EXPORT OF REFINED BLEACHED DEODORIZED (RBD) OLEIN - Kustiari, Reni; Rumagit, Grace (Journal of Indonesian Economy and Business, 2009)
Indonesia needs to increase its export products in order to maintain surplus balance of payment. However, Pakistan-Malaysia FTA could make Indonesian RBD Olein in adifficult situation. This paper aims to examine the impact of a decrease in import tariff of Malaysian RBD olein in Pakistan on Indonesian export of RBD Olein using Trade analysisemploying Armington model that distinguishes the product by the country of origin. RBD olein trade model consists of four endogenous countries and one exogenous rest of theworld (ROW). The endogenous countries are Indonesia, Malaysia, the United State of America and Pakistan. The results indicate that the reduction in import tariff of Malaysian RBD Olein by 10 percent will cause the price to decrease by around 7.3 percent. The decline in Malaysian RBD olein price will increase its demand in Pakistan by around 4.4 percent. While import demand of Indonesian RBD Olein in Pakistan estimated to increase by only 0.35 percent, this is because the price of Indonesian RBD Olein rises by 0.17percent. In other word, calculated based on the average of export volume and implicit price in the period 2005-2007, import of Indonesian RBD Olein in Pakistan will only increase by around 2.1 thousand tones, or US$ 1.03 million,.Keywords: tariff, import, export, Armington model.